Recent Progress in Metal Nanowires for Flexible Energy Storage Devices - Wang, Junxiang; Piao, Wenxiang; Jin, Xuanzhen; Jin, Long Yi; Yin, Zhenxing (Frontiers in Chemistry, 2022)
With the rapid evolution of wearable electronics, the demand for flexible energy storage devices is gradually increasing. At present, the commonly used energy storage devices in life are based on rigid frames, which may lead to failure or explosion when mechanical deformation occurs. The main reason for this phenomenon is the insufficient elastic limit of the metal foil current collector with a simple plane structure inside the electrodes. Obviously, the design and introduction of innovative structural materials in current collectors is the key point to solving this problem. Several recent studies have shown that metal nanowires can be used as novel current collector materials to fabricate flexible energy storage devices. Herein, we review the applications of metal nanowires in the field of flexible energy storage devices by selecting the three most representative metals (Au, Ag, and Cu). By the analysis of the various typical literature, the advantages and disadvantages of these three metal nanowires (Au, Ag, and Cu) are discussed respectively. Finally, we look forward to the development direction of one-dimensional (1D) metal nanowires in flexible energy storage devices and show the personal opinions with a reference value, hoping to provide the experience and ideas for related research in the future.